Fungal spore distribution in two hospitals in Kabale district, Uganda - Gerald, Niwamanya; Odebode, Adeyinka (Journal of Experimental Sciences, 2022)
Fungi infections are a danger to the value of human life as they cause health issues such as depression, lack of self-confidence and seclusion in infected individuals. To date, the prevalence and distribution of airborne fungi spores are still not well documented in Uganda. Airborne fungi spores in Kabale Referral and Rugarama hospitals were monitored for two months. This study also examined the proportion of fungal infection cases reported in the two hospitals regularly. The fungal colonies were collected for two months using the open plate sedimentation method with Petri dishes of Potato Dextrose Agar (PDA) media, cultured and identified morphologically. The obtained results were analyzed using analysis of variance (ANOVA) and means were separated using Duncan Multiple Range Test (DMTR) with a level of significance at P<0.05. A total of 398 fungal colonies were obtained from the two locations for the period of study. Aspergillus flavus (15.3%) followed by Aspergillus fumigatus (10.6%) recorded the highest number of fungal colonies while Nigrospora (1%), Fusarium spp,(2.3%) and Trichoderma spp, (1.3%) had the least number of species in all the locations sampled. A number of the fungi isolated are opportunistic and are allergens that cause various diseases, irritations and allergic reactions in humans. Therefore, this study recommends routine aerobiological monitoring in both outdoor and indoor hospital environments for better management of fungal infections.